Successful outcome of first paediatric renal transplant for HIV associated nephropathy. (24th May 2012) - Shroff, R; McCulloch, M; Novelli, V; Shingadia, D; Clapson, M; Jagani, M; Patey, S; Mamode, M; Sebire, N; Bradley, S; Marks, S
Abstract : Aims: Classical HIV-associated nephropathy (HIVAN) was first described before the advent of highly active anti-retroviral therapy (HAART) in late stages of HIV disease with high viral load and low CD4+ cell count. Renal transplantation guidelines for adults with HIVAN have been developed1 with comparable patient and graft survival.2 3 We report the successful outcome of living related renal transplantation in an 8 year old girl (AB; name changed) on haemodialysis due to HIVAN. Patients and methods: AB is a vertically HIV-infected girl who was initially lost to follow-up but represented aged 5.5 years with lymphocytic interstitial pneumonitis (LIP) and CDC stage.1 She was not initially commenced on HAART but subsequently developed acute renal failure and renal biopsy confirmed HIVAN. Hemodialysis and HAART (Lopinavir/ritonavir, lamivudine and abacavir) were started at 6.5 years. Results: Pre-transplantation screening showed an undetectable HIV-1 viral load and CD4 counts of 43% (=1990/mm 3 ). She underwent living related renal transplantation from her 56-year old maternal grandmother (mismatch 1, 1, 1; donor and recipient both CMV negative and EBV positive). There was a historical B-cell positive cross-match, and she was therefore treated as a 'high-risk' transplant using induction therapy with basiliximab, tacrolimus, mycophenolate mofetil and steroids. Tacrolimus was started six weeks prior to transplantation in order to stabilise levels. HAART (Lopinavir/ritonavir, abacavir and lamivudine) was continued together with isoniazid, azithromycin, co-trimoxazole and fluconazole prophylaxis. Currently, she is 2 months post-transplant with excellent allograft function - plasma creatinine 41-48 µmol/l; estimated glomerular filtration rate 80-94 mls/min/1.73m 2 . She has mild hypertension requiring two anti-hypertensive agents and low-grade albuminuria (25 mg/mmol). Therapeutic tacrolimus levels are achieved with once-daily tacrolimus given 5-days per week only. She has an undetectable HIV-1 viral load and CD4+ counts of 240/mm 3 . Protocol biopsy at 6 weeks shows mild chronic changes, no donor specific antibodies and normal transplant renal ultrasound. There have been no HIV-related complications. Conclusion: This is the first reported case of successful renal transplantation in a child with HIVAN in the UK. Adult experience suggests higher risk of rejection and careful monitoring for long-term HIV-associated complications.3